Retinol Dehydrogenase 10 but Not Retinol/Sterol Dehydrogenase(s) Regulates the Expression of Retinoic Acid-responsive Genes in Human Transgenic Skin Raft Culture - Lee, Seung-Ah (American Society for Biochemistry and Molecular Biology, 2011)
Retinoic acid is essential for skin growth and differentiation, and its concentration in skin is controlled tightly. In humans, four different members of the short-chain dehydrogenase/reductase (SDR) superfamily of proteins were proposed to catalyze the rate-limiting step in the biosynthesis of retinoic acid (the oxidation of retinol to retinaldehyde). Epidermis contains at least three of these enzymes, but their relative importance for retinoic acid biosynthesis and regulation of gene expression during growth and differentiation of epidermis is not known. Here, we investigated the effect of the four human SDRs on retinoic acid biosynthesis, and their impact on growth and differentiation of keratinocytes using organotypic skin raft culture model of human epidermis. The results of this study demonstrate that ectopic expression of retinol dehydrogenase 10 (RDH10, SDR16C4) in skin rafts dramatically increases proliferation and inhibits differentiation of keratinocytes, consistent with the increased steady-state levels of retinoic acid and activation of retinoic acid-inducible genes in RDH10 rafts. In contrast, SDRs with dual retinol/sterol substrate specificity, namely retinol dehydrogenase 4 (RoDH4, SDR9C8), RoDH-like 3α-hydroxysteroid dehydrogenase (RL-HSD, SDR9C6), and RDH-like SDR (RDHL, SDR9C4) do not affect the expression of retinoic acid-inducible genes but alter the expression levels of several components of extracellular matrix. These results reveal essential differences in the metabolic contribution of RDH10 versus retinol/sterol dehydrogenases to retinoic acid biosynthesis and provide the first evidence that non-retinoid metabolic products of retinol/sterol dehydrogenases affect gene expression in human epidermis.